PERENCANAAN STRATEGIS SISTEM DAN TEKNOLOGI INFORMASI PADA PT ELODA MITRA - Ni Luh Septiana Dharmayanti; Pantjawati Sudarmaningtyas; Yoppy Mirza Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2018)
The main activities of PT.Eloda Mitra have used application in daily activities, but those applications are still based on each division. This will cause the business processes become uncontrollable and data in each division is not integrated. A way to solve the problem in PT. Eloda Mitra is with strategic planning with Anita Casidy method, where in the planning started from upstream to downstream of the company. Anita casidy method having 4 (four) stage that are visioning, analysis, direction, recommendation. The result of that method is IS strategy, IT strategy dan IT management. Results of this research are as follows, IS Strategy that are repairing vendor ordering system by using STI, making customer complain centre, making STI data security system, making changes SDM system which the recruitment of new staff to making standard operating procedure, and updating the website. The result of thi method also obtain IT strategy that are apply a system of management equipment repair for improve network management, increased clustering activity and SANs, Review the design and the use of data center to ensure discharging that can save, using PDA in business process. IT management for supporting IS and IT strategy is composing management human resources for all planning and conduct training human resources